1993
DOI: 10.1021/ma00069a042
|View full text |Cite
|
Sign up to set email alerts
|

Conformational contraction and hydrolysis of hyaluronate in sodium hydroxide solutions

Abstract: The effects of NaOH on the conformations, interactions, diffusion, and hydrolysis rates of hyaluronate (HA) were characterized in detail using static light scattering (i) in the traditional "batch" mode (for conformations and interactions), (ii) in a time-dependent, simultaneous multiangle mode (for the hydrolysis rates), and (iii) coupled to HPLC for preliminary characterization of distributions of hydrolysis fragments. Strikingly, the conformations, interactions, and hydrolysis rates all seem to be controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 11 publications
6
37
0
Order By: Relevance
“…0.5%), to study the effect of more concentrated salt solutions, to check the effect of temperature and pressure, and of other physico-chemical triggers for controlling the viscosity of the frac fluid in the different stages of the life of a basin. Uncited references Gosh et al (1993), Lo Nostro et al (2010, Morris et al (1980), Sawayama and Kawabata (1991), Sasaki (2002), Scott and Tigwell (1975), Scott and Tigwell (1977), Setschenow (1889), Sheehan et al (1977) and Yudianti et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…0.5%), to study the effect of more concentrated salt solutions, to check the effect of temperature and pressure, and of other physico-chemical triggers for controlling the viscosity of the frac fluid in the different stages of the life of a basin. Uncited references Gosh et al (1993), Lo Nostro et al (2010, Morris et al (1980), Sawayama and Kawabata (1991), Sasaki (2002), Scott and Tigwell (1975), Scott and Tigwell (1977), Setschenow (1889), Sheehan et al (1977) and Yudianti et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…They assumed the existence of a critical balance between the repulsive forces (provided by the ionized carboxyl groups) and the attractive interactions (electrostatic or hydrogen bonds mediated) operating between the molecular chain elements. At alkaline pH, hydrogen bonds taking part in the structural organization of HA chains are destroyed and this results in a large loss of the intrinsic stiffness and the formation of a more compact, flexible random coil (Ghosh et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Theory and application to random scission of single-strand polymers was detailed in several publications. [27][28][29][30][31] It was shown that the technique could be used to rapidly and accurately determine Michaelis-Menten-Henri parameters, 27 to investigate the enhanced degradability of copolymers, 29 to determine sidechain branching and multiple modes of degradation, 32 and to make other structural and mechanistic determinations (multiple strands). 33 A more general formalism for deriving TDSLS signatures of degrading polymers was also introduced.…”
Section: Introduction Galactomannansmentioning
confidence: 99%